Nutritional Characterization of Street Food in Urban Turkmenistan, Central Asia - Albuquerque, Gabriela; Sousa, Sofia; Lança de Morais, Inês; Gelormini, Marcello; Motta, Carla; Gonzales, Gerard Bryan; Ovezov, Azat; Damasceno, Albertino; Moreira, Pedro; Breda, João; Lunet, Nuno; Padrão, Patrícia (Frontiers in Public Health, 2022)
Objective: Describing the availability and nutritional composition of the most commonly available street foods in Ashgabat, Turkmenistan. Methods: 161 street food vending sites (six public markets) were assessed, through collection of data on vending sites’ characteristics and food availability, and samples of commonly available foods (21 homemade; 11 industrial),for chemical analysis. Results: Fruit, beverages and food other than fruit were available in 6.8%, 29.2% and 91.9% of all vending sites. Regarding the latter, 52.7% of the vending sites sold only homemade (main dishes, snacks, cakes, biscuits and pastries, bread, ice-cream, chocolate and confectionery, savoury pastries and sandwiches), 37.2% only industrial (ice-cream, chocolate and confectionery, cakes, biscuits and pastries, snacks, bread and savoury pastries) and 10.1% both. Homemade foods presented higher total fat, monounsaturated, polyunsaturated and trans-fat, and sodium and potassium content. Industrial wafers presented the highest mean saturated (11.8 g/serving) and trans-fat (2.32 g/serving) content. Homemade hamburger presented the highest mean sodium content (1889 mg/serving). Conclusions: Strategies to encourage the production and sales of healthier street foods, especially homemade, are needed to promote healthier urban food environments in urban Turkmenistan.